Кон Miranda Fricker and Jennifer Hornsby (Eds.), The Cambridge Companion to Feminism in Philosophy: Për Miranda Fricker and Jennifer Hornsby (Eds.), The Cambridge Companion to Feminism in Philosophy - Ivanovska, Marija; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2005)
Author(s): Marija Ivanovska | Марија Ивановска Title (Macedonian): Кон Miranda Fricker and Jennifer Hornsby (Eds.), The Cambridge Companion to Feminism in Philosophy Title (Albanian): Për Miranda Fricker and Jennifer Hornsby (Eds.), The Cambridge Companion to Feminism in Philosophy Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 355-356 Page Count: 2 Citation (Macedonian): Марија Ивановска, „Кон Miranda Fricker and Jennfer Hornsby (Eds.), The Cambridge Companion to Feminism in Philosophy“, Идентитети: списание за политика, род и култура, т. 4, бр. 1-2 (лето - зима 2005): 355-356. Citation (Albanian): Marija Ivanovska, „Për Miranda Fricker and Jennfer Hornsby (Eds.), The Cambridge Companion to Feminism in Philosophy“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005): 355-356.